A Comparison Study of Fiber Diameter's Effect on Characteristic Features of Donepezil/Curcumin‐Loaded Polycaprolactone/Polylactic Acid Nanofibers. Issue 5 (17th May 2022) - Aydin, Saliha; Kabaoglu, Ilke; Guler, Ece; Topal, Fadime; Hazar‐Yavuz, Ayse Nur; Ekentok, Ceyda; Tatar, Esra; Gurbuz, Fatmanur; Gunduz, Oguzhan; Cam, Muhammet Emin
Abstract : Back Cover : In article number 2100855, Muhammet Emin Cam and co‐workers present the drugs curcumin (orange) and donepezil (green), which are used for the treatment of Alzheimer's disease, which are released from nanofibers that have three different diameters (the largest, medium, and thinnest). The percentage of burst drug release from nanofibers is augmented by the increase of fiber diameter. Designed by Ece Guler and drawn by Bilge Tuzcu.